Uncoupling of oxidative phosphorylation and antioxidants affect fusion of primary human myoblasts in vitro - Zakharova, V.V.; Dib, C.; Saada, Y.B.; Vassetzky, Y.S.; Galkin, I.I.; Chernyak, B.V.; Popova, E.N. (Вiopolymers and Cell, 2016)
Reactive oxygen species are at the origin of muscular fatigue and atrophy. They are also linked to muscular dystrophies, a group of human genetic diseases. Several studies point to the benefits of application of antioxidants and uncouplers of oxidative phosphorylation to improve the functional activity of normal and pathological muscles. Other studies point to potential dangers of these compounds. Aim. To study the effect of mitochondria-targeted antioxidants and uncouplers of oxidative phosphorylation on muscle differentiation. Methods. Muscle differentiation was induced by serum starvation and monitored by troponin T staining. Results. the mitochondria-targeted uncoupler of oxidative phosphorylation C12TPP, but not the mitochondria-targeted antioxidant SkQ1, inhibit fusion of primary myoblasts upon their differentiation, but do not affect the synthesis of troponin T, a protein marker of muscle differentiation. Conclusion. The effect of C12TPP could be at least partially mediated by inhibition of reactive oxygen species (ROS) production since antioxidant N-acetylcysteine at high doses also inhibited differentiation of myoblasts.